Does Religion/Spirituality Modify the Association of Stressful Life Events and Suicidal Ideation in Australian Men? - Krysinska, Karolina (Religions, 2018)
In a large population cohort of Australian men, we previously observed that stressful life events were associated with increased suicidal ideation (SI). Many stressful life events, such as relationship breakdown and financial difficulties, occur frequently, yet most men who experience them do not have suicidal thoughts. There is some evidence that religious belief may be protective against suicidal behaviour. This study examined if attendance of religious service and/or perceived importance of religion/spirituality to participants modifies the association between stressful life events and suicidal thinking. Our analysis included 10,588 men who were aged 18 years or older who participated in the Australian Longitudinal Study on Male Health (Ten to Men), a national cohort study of Australian males. The study compared demographic, protective and risk factors for four subgroups: No SI, Remitted SI, New SI, and Chronic SI between Wave 1 (October 2013 to July 2014) and Wave 2 (November 2015 to May 2016) of the study and conducted logistic regression for these four outcomes. The study found a protective effect for attendance of religious services for the onset of New SI at Wave 2. Importance of religion/spirituality was positively related to Chronic SI. There were no effects of service attendance or importance for any of the other SI outcomes. We discuss results of the study in relation to social connection and broader contextual factors, such as secularization.